Variations of dengue shock syndrome cases and their management: report of three cases - Gede Bagus Mahendra Wirajaya; Ayu Agung Pradnya Paramitha Dwi Sutanegara; Desak Nyoman Desy Lestari (DiscoverSys Inc., 2022)
Background: Dengue hemorrhagic fever (DHF) occurs due to plasma leakage due to increased vascular permeability, which is also supported by an active complement system, which makes DHF fall into complications such as shock or dengue shock syndrome (DSS). The comprehensive management of DSS could prevent morbidity and mortality in patients. We aimed to report three variations of dengue shock syndrome cases and their management. Case presentation: Three cases of DSS from our hospital. Two case reports with clinical dengue fever patients with shock and one case report with clinical dengue patients with shock and complications of acute liver failure. The first case was a 24 years olds male patient with classic signs of dengue fever plus spontaneous bleeding in the form of nosebleeds accompanied by hemodynamic disturbances. Laboratory examination revealed severe thrombocytopenia. In the second case, a male patient with dengue shock syndrome accompanied acute liver failure. The patient complains of heartburn and nausea accompanied by tea-like urine. Dengue patients with abdominal pain typical of liver disorders, nausea, vomiting and anorexia, and hepatomegaly with or without jaundice are typical of liver disorders. The third case, a male patient with dengue shock syndrome, accompanied the suspicion of ascites. The main treatment is the administration of isotonic crystalloid fluids according to body weight. While in cases of acute liver failure, NAC can be given. Conclusion: We found three cases of DSS with some complications. It is important to know the right treatment immediately so that complications do not occur.